Mental Development and Personality Development in Preschool Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Various methods and activities are used for the development of psyche and consciousness and the development of the child's personality in preschool children. One of them, first of all, is a game. Drawing, competitions and fairy tales play an important role in the child's mental development. This article talks about the child's mental and personal development.